Opportunities, Limitations and Gaps in the Ecological Restoration of Drylands in Argentina - Busso, C A; Perez, D R (Annals of Arid Zone, 2019)
This paper reviews the opportunity to ecologically restore, impaired dryland ecosystems in Argentina. This is very important because they contribute to (1) control the effects of desertification in the country, and (2) reverse the complex social consequences of the degradation. Reported benefits and limitations, as well as gaps, in the ecological restoration of drylands in Argentina, where more than 67% of continental lands are arid and semi-arid territories are affected by abusive (and inadequate) utilization are discussed. The selected restoration case studies on drylands in the country were grouped into: (1) prescribed natural regeneration, and (2) assisted natural regeneration, partial reconstruction and (3) complete restoration. Based on comparison of results from other drylands of the world there may be possibilities of applying some practices to fill the ecological gaps. Finally, there is an analysis of costs and benefits, monitoring procedures and potential for application of useful new techniques as levels of intervention are increased. Key words: Branching, direct seeding, natural regeneration, plantation, topsoil.